Optimization conditions of UV-C radiation combined with ultrasound-assisted extraction of cherry tomato (Lycopersicon esculentum) lycopene extract - Alexandre R. Lima; Nathana L. Cristofoli; Josamaique G. Veneral; Alcilene R. M. Fritz; Margarida C. Vieira (International Journal of Food Studies)
The aim of this work was to study the effect of UV-C radiation on ultrasound assisted extraction (UAE) of cherry tomato bioactive compounds. Cherry tomatoes were exposed to two UV-C radiation doses (0.5 and 1.0 J cm−2 ) and stored at 20 ± 0.5 oC for 7 days. Next, they were lyophilized, and the bioactive compounds were extracted by UAE at 20 KHz. To evaluate the effectiveness of the extraction process of the bioactive compounds, a CCRD (central composite rotational design) was used together with RSM (response surface methodology), for extraction times from 4 to 12 minutes and concentrations (g of lyophilized product / L of ethanol) of 1:10, 1:20 and 1:30. The extracts obtained from the irradiated tomatoes presented 5.8 times more lycopene content than the controls and higher antioxidant activity was obtained for 4 and 8 min, in the concentrations 1:10 and 1:20 (m v −1 ). Through numerical model optimization, optimal extraction conditions were obtained. The results demonstrated that by previously irradiating tomatoes with UV-C light, the UAE yielded considerably higher amounts of lycopene and other bioactives.